DESCRIPTION OF THE LEVEL OF ANXIETY IN POST PARTUM - Alfya Lailatul Istiqomah; Nurya Viandika; Shofia Maharani Khoirun Nisa (Indonesian Midwifery and Health Sciences Journal, 2021)
Background: The puerperium begins when the baby and placenta are born until the uterus returns to its pre-pregnancy state, and generally lasts for 6 weeks. There are several adaptations that must be passed by postpartum  period including physiological, psychological and social. Anxiety is part of the psychological disorders of postpartum mothers, if anxiety is not handled it can cause postpartum blues and its impact causes a decrease in children's cognitive abilities compared to their peers. The purpose of this study was to describe the level of anxiety in post partum mothers at HJ Faridatul Ampera S.Tr. Keb Independece Midwifery Practice Malang Regency. Methods: The method used in this research is descriptive quantitative with a sample of 38 postpartum mothers with purposive sampling method. The instrument used was a questionnaire, with postpartum mother's anxiety variable. Results: All post partum  (100%) experienced anxiety with a mild level of anxiety of 50.00%, experiencing moderate anxiety of 36.84% and experiencing severe anxiety of 13.16%. Conclusion: Post partum maternal anxiety can occur due to various factors, therefore comprehensive support and care are needed in dealing with the post partum mother adaptation period.